Biomarker Expression in Multifocal Vulvar High-Grade Squamous Intraepithelial Lesions - Nikki B. Thuijs (MDPI AG, 2021)
In patients with high-grade squamous intraepithelial lesion (HSIL) of the vulva, the presence of multiple lesions, called multifocal HSIL, is common. The aim of this exploratory study was to investigate biomarker expression profiles in multifocal HSIL. In total, 27 lesions from 12 patients with high-risk human papillomavirus (HPV)-positive multifocal HSIL were tested for HPV genotype, expression of p16INK4a and Ki-67, and DNA methylation of six genes. HPV16 was found most commonly in 21 (77.8%) HSILs. In two (16.4%) patients, HPV genotype differed between the lesions. All lesions demonstrated diffuse p16INK4a staining, of which three (11.1%) were combined with patchy staining. One patient (8.3%) demonstrated markedly different DNA methylation levels between lesions. Generally, heterogeneity in methylation profiles was observed between different patients, even when other biomarkers showed similar expression. In conclusion, this study is the first to demonstrate heterogeneity of individual lesions in patients with multifocal HSIL. The studied biomarkers have the potential to refine prognostic and predictive diagnostics. Future prospective, longitudinal studies are needed to further explore the potential of a biomarker profile for management of patients with multifocal HSIL.